An evolutionary view of the Fusarium core genome (2024)
ABSTRACT: Fusarium, a member of the Ascomycota fungi, encompasses several pathogenic species signifcant to plants and animals. Some phytopathogenic species have received special attention due to their negative economic impact on the agricultural industry around the world. Traditionally, identifcation and taxonomic analysis of Fusarium have relied on morphological and phenotypic features, including the fungal host, leading to taxonomic conficts that have been solved using molecular systematic technologies. In this work, we applied a phylogenomic approach that allowed us to resolve the evolutionary history of the species complexes of the genus and present evidence that supports the F. ventricosum species complex as the most basal lineage of the genus. Additionally, we present evidence that proposes modifcations to the previous hypothesis of the evolutionary history of the F. staphyleae, F. newnesense, F. nisikadoi, F. oxysporum, and F. fujikuroi species complexes. Evolutionary analysis showed that the genome GC content tends to be lower in more modern lineages, in both, the whole-genome and coregenome coding DNA sequences. In contrast, genome size gain and losses are present during the evolution of the genus. Interestingly, core genome duplication events positively correlate with genome size. Evolutionary and genome conservation analysis supports the F3 hypothesis of Fusarium as a more compact and conserved group in terms of genome conservation. By contrast, outside of the F3 hypothesis, the most basal clades only share 8.8% of its genomic sequences with the F3 clade.